Complement C3-Deficient Mice Fail to Display Age-Related Hippocampal Decline - Shi, Qiaoqiao; Colodner, Kenneth J; Matousek, Sarah B; Merry, Katherine; Hong, Soyon; Kenison, Jessica E; Frost, Jeffrey L; Le, Kevin X; Li, Shaomin; Dodart, Jean-Cosme; Caldarone, Barbara J; Stevens, Beth; et al. (The Journal of neuroscience, 2015)
The complement system is part of the innate immune response responsible for removing pathogens and cellular debris, in addition to helping to refine CNS neuronal connections via microglia-mediated pruning of inappropriate synapses during brain development. However, less is known about the role of complement during normal aging. Here, we studied the role of the central complement component, C3, in synaptic health and aging. We examined behavior as well as electrophysiological, synaptic, and neuronal changes in the brains of C3-deficient male mice (C3 KO) compared with age-, strain-, and gender-matched C57BL/6J (wild-type, WT) control mice at postnatal day 30, 4 months, and 16 months of age. We found the following: (1) region-specific and age-dependent synapse loss in aged WT mice that was not observed in C3 KO mice; (2) age-dependent neuron loss in hippocampal CA3 (but not in CA1) that followed synapse loss in aged WT mice, neither of which were observed in aged C3 KO mice; and (3) significantly enhanced LTP and cognition and less anxiety in aged C3 KO mice compared with aged WT mice. Importantly, CA3 synaptic puncta were similar between WT and C3 KO mice at P30. Together, our results suggest a novel and prominent role for complement protein C3 in mediating aged-related and region-specific changes in synaptic function and plasticity in the aging brain. Significance statement: The complement cascade, part of the innate immune response to remove pathogens, also plays a role in synaptic refinement during brain development by the removal of weak synapses. We investigated whether complement C3, a central component, affects synapse loss during aging. Wild-type (WT) and C3 knock-out (C3 KO) mice were examined at different ages. The mice were similar at 1 month of age. However, with aging, WT mice lost synapses in specific brain regions, especially in hippocampus, an area important for memory, whereas C3 KO mice were protected. Aged C3 KO mice also performed better on learning and memory tests than aged WT mice. Our results suggest that complement C3, or its downstream signaling, is detrimental to synapses during aging.